Quantificação e formas de atenuação dos níveis de ruído gerados pelo uso da betoneira - Ribeiro, Silvio Cesar (2014)
The concrete mixers, although seemingly harmless and equipment that do not bring many risks to workers, hides a very serious problem associated with their operation, which are the high levels of noise produced. Usually the mixers operators are those that are more exposed to these high levels of noise and there are also other operators and the neighborhood. This research and to quantify these impacts, suggests ways to mitigate the noise levels assimilated by these mixers operators and discharged from this equipment, acting at the source. To minimize the noise level cap has been developed for use in the mouth of the barrel, so it does not interfere with the mixer operating mode and also serve to reduce the noise when mixing the aggregate. Object of study was the analysis and application of two materials, namely plates EVA and liquid rubber, to drum coating the mixer, which would help reduce the noise level. The equivalent sound pressure levels were collected in front, behind and on the sides of the mixer at distances 1-8 meters. The results showed that it is possible to minimize noise ensuring acoustic comfort while using the mixer on a construction site. Tests have shown that among the options considered, is the best coating liquid rubber which may be used externally to the mixer drum 13 reducing the noise in dB (A), reaching 17 dB (A) with the use of lid protection.